Reinvenção do educador: literatura e hipermídia - Mathias, Arlete Aparecida (2018)
In the doctoral thesis, in Digital Design Intelligence Technologies, The Reinvention of the Educator: literature and hypermedia, the author with simultaneous goal of subject researcher and researched subject is based on the methodology life histories to analyze the process of reinvention of her pedagogical practice along of her teaching career, especially in the area of literature and hypermedia. In the role like a researcher, she uses like a source material her own trajectory and experience from the researched subject, and about it she has conscious from her importance in the formative processes as a possibility of self-knowledge or a path that gives herself a kind of self learning power. Such as severval life histories authors she finds referential support in Marie-Christine Josso ´s reseachers (2004) in an alliance with the Complexity / Transdisciplinarity method, worked by Edgar Morin; so she thinks without disjunction and without reductionism the production of a knowledge derived from her subjective experiences, the philosophical, political, cultural, the characteristics of the general society from the narrative that she is inserted. This is the way that the datas from her narratives are reintroduced in his research-formation as a source of self-knowledge and (self) formation of her trajectories experienced and brings her hints and vision comprehension like a subject researcher in the current world. This thesis / research-formation is not an isolated object, because as its author in my bibliographic review I found other formation researches that chose the same way construction through inexhaustible relational dialogue between subject-object, practice and theory. Marie-Christine Josso in 1983, like me, also, chose to build up her research-formation through her doctoral thesis so, she was simultaneously, as subject researcher and researched subject built herself Walk in order the defense a method that became reference from her research - formation and spread to several fields, including for the education. Reasoning in a complex way the strategies of her method in unit with other self-forming studies, new perspectives of meditation have emerged to rescue my sleeping pedagogies in the bowels of my being. So they became the reflections that brought afloat the discovery of this method of (self) formation that I materialized this written text composition in order of the defense from this doctoral thesis The Reinvention of Educator: literature and hypermedia. I understand, now, the context of the arguments of this research-formation like a singular / plural synonym from several processes of reinvention and formation throughout my life; relationship with my students, the world and with the human way of life. So, I consider, this research-formation result like a resumption of self- knowledge, a consciousness not only of my constant (self) formation and reinvention, but an unfinished clearing values’, uncertainties’, beliefs’, conceptions’, histories, and open ideas for other researching teachers, people, inside or outside the literature hypermedia field